2020
DOI: 10.1166/jnn.2020.17159
|View full text |Cite
|
Sign up to set email alerts
|

Photoresponses of Zinc Tin Oxide Thin-Film Transistor

Abstract: In this study, the optical and electrical properties of a zinc tin oxide (ZTO) thin-film transistor (TFT) were investigated. The TFT was fabricated using ZTO as the active layer, which was deposited by a radio frequency magnetron sputtering system, to form an ultraviolet (UV) photodetector. The device has a threshold voltage of 0.48 V, field-effect mobility of 1.47 cm2/Vs in the saturation region, on/off drain current ratio of 2×106, and subthreshold swing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The μ and SS of the solution-processed Z/S/Z TFT proposed in this work are 14.33 cm 2 V −1 s −1 and 0.13 V dec −1 , respectively, which are also better than the values of 1.47–6.1 cm 2 V −1 s −1 and 0.15–1.39 of the sputtered ZTO TFTs reported in the literature. 21,22,34–36 The above comparison indicates that this study has a significant advancement in ZTO-based TFT technology. The performance of the proposed Z/S/Z TFT is higher than most ZTO-based TFTs fabricated using solution and vacuum sputtering processes.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…The μ and SS of the solution-processed Z/S/Z TFT proposed in this work are 14.33 cm 2 V −1 s −1 and 0.13 V dec −1 , respectively, which are also better than the values of 1.47–6.1 cm 2 V −1 s −1 and 0.15–1.39 of the sputtered ZTO TFTs reported in the literature. 21,22,34–36 The above comparison indicates that this study has a significant advancement in ZTO-based TFT technology. The performance of the proposed Z/S/Z TFT is higher than most ZTO-based TFTs fabricated using solution and vacuum sputtering processes.…”
Section: Resultsmentioning
confidence: 74%
“…This may overcome the bottleneck of m for ZTO-based TFT devices. [20][21][22]29,30,[34][35][36][37][38][39][40]80,81…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the parameter optimization, the TFT devices with the ZATO films performed at the 623 K annealing with an Ion/Ioff ratio of 5.55 × 10 7 , an SS value of 0.15 V/decade and a saturation mobility (μsat) of 3.73 cm 2 •V −1 •s −1 . On the basis of the results, the ZATO TFTs show better properties compared to the ZTO TFTs of 2 × 10 6 , 0.45 V/decade and 1.47 cm 2 •V −1 •s −1 by Lun et al [40]. Besides, the SnO2 materials have hygroscopicity, which may reduce the stability of the TFT.…”
Section: Characterization Of Zato Tfts With Different Annealing Tempe...mentioning
confidence: 87%
“…For example, Martins et al demonstrated Indium-Zinc-Oxide (IZO) TFT with enhanced performances compared with ZnO TFT [11]. Other alloy oxide compounds such as ZTO [12], IGZO [3,13], ITZO [14,15], AZO [16,17], GZO [18,19] etc. have also been published.…”
Section: Introductionmentioning
confidence: 99%